The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1983-1447.2021.20200247
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and diabetes mellitus: sociodemographic and clinical profile in Brazilian municipalities

Abstract: Objective To analyze the sociodemographic and clinical profile of tuberculosis cases with Diabetes Mellitus in Brazilian municipalities in the states of São Paulo, Paraná and Rio Grande do Norte. Method This is a cross-sectional study, whose population consisted of tuberculosis cases notified between 2010 and 2014. Data were collected from secondary sources. In the data analysis, descriptive analysis and multiple correspondence analysis techniques were used. Results The prevalence of diabetes among tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…( Martinez et al., 2012 ) also found less immigrants with diabetes mellitus. Although studies report that patients with this disease have greater probability of becoming sick from TB ( Beraldo et al., 2021 ; Demlow et al., 2015 ), such contrariness may be justified by the younger age of the immigrant population analyzed in this study and since an association between TB and diabetes is more frequently found in the age range between 50 and 69 years ( Suwanpimolkul et al., 2014 ).…”
Section: Discussionmentioning
confidence: 77%
“…( Martinez et al., 2012 ) also found less immigrants with diabetes mellitus. Although studies report that patients with this disease have greater probability of becoming sick from TB ( Beraldo et al., 2021 ; Demlow et al., 2015 ), such contrariness may be justified by the younger age of the immigrant population analyzed in this study and since an association between TB and diabetes is more frequently found in the age range between 50 and 69 years ( Suwanpimolkul et al., 2014 ).…”
Section: Discussionmentioning
confidence: 77%
“…Horizonte, Imperatriz e Campina Grande (ROCHA et al, 2016;SOUSA et al, 2021;LACERDA et al, 2016). No entanto, há um estudo realizado em São Paulo, Paraná e Rio Grande do Norte que apresentou resultados divergentes, apontando para uma maior prevalência da comorbidade em indivíduos do sexo feminino entre os anos de 2010 e 2014 (BERALDO et al, 2021).…”
Section: Resultsunclassified
“…Estudos indicam que ser mulher pode ser um fator de risco, devido à má utilização dos serviços de saúde, ao papel de cuidador para os doentes e à influência do estrogênio na produção de citocinas durante a infecção por TB (WORKNEH et al, 2017). Quando analisado em relação à faixa etária, foi observado uma maior concentração de casos de tuberculose em indivíduos com idade entre 40 e 59 anos (n= 670; 52,5%) (Tabela 1), corroborando com outros estudos (LACERDA et al, 2016;BERALDO et al, 2021;ABREU et al, 2020). No entanto, pesquisas recentes têm apontado um aumento do número de casos em indivíduos com mais de 60 anos (SOUSA et al, 2021), que pode estar relacionado a uma série de fatores.…”
Section: Resultsunclassified
See 1 more Smart Citation